Practicality of student worksheet oriented to higher order thinking skills on biology subject for grade XI - Nur Afni; Adnan Adnan; Nurhayati B (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
Students must possess higher-order thinking skills (HOTS) as a demand for 21st century competence. Teachers need to prepare teaching materials that can place high-level thinking students in solving the problems they face. One of the learning tools to solve these problems is the HOTS-oriented worksheets (LKPD). This study aimed to test the practicality of HOTS-oriented worksheets in biology subjects in the even semester of class XI at SMAN 1 Barru. This type of research is Research and Development (R&D) with the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. The instruments used were product implementation observation sheets and teacher and student response questionnaires. HOTS-oriented worksheets was implemented at SMA Negeri 1 Barru with research subjects, namely three biology teachers and 33 students in class XI MIPA 2. The results showed that the percentage of the practicality of HOTS-oriented worksheets through product implementation was 4.23 (practical), the teacher's response was 4.51 ( practical), and student responses of 4.02 (practical). Overall, the HOTS-oriented worksheets are classified as practical. Further research is expected to train students' HOTS to meet the demands of 21st century competencies and better learning outcomes.Abstrak Keterampilan berpikir tingkat tinggi (HOTS) merupakan salah satu yang wajib dimiliki oleh peserta didik sebagai tuntutan kompetensi abad-21. Guru perlu menyiapkan bahan ajar yang mampu menempatkan peserta didik berpikir tingkat tinggi dalam memecahkan permasalahan yang dihadapinya. Salah satu perangkat pembelajaran untuk memecahkan permasalahan tersebut adalah Lembar Lembar Kerja Peserta Didik (LKPD) berbasis HOTS. Tujuan penelitian ini adalah menguji kepraktisan LKPD berbasis HOTS pada mata pelajaran biologi semester genap kelas XI di SMAN 1 Barru. Jenis penelitian ini adalah Research and Development (R&D) dengan model pengembangan ADDIE yang meliputi analisis, perancangan, pengembangan, implementasi, dan evaluasi. Instrumen yang digunakan yaitu lembar observasi keterlaksanaan produk, angket respon guru, dan angket respon peserta didik. Implementasi LKPD berbasis HOTS dilaksanakan di SMA Negeri 1 Barru dengan subjek penelitian yaitu tiga guru mata pelajaran biologi dan 33 peserta didik kelas XI MIPA 2. Hasil penelitian menunjukkan persentase kepraktisan LKPD berbasis HOTS melalui keterlaksanaan produk sebesar 4,23 (praktis), respon guru sebesar 4,51 (praktis), dan respon peserta didik sebesar 4,02 (praktis). Secara keseluruhan LKPD berbasis HOTS ini tergolong praktis. Penelitian lanjutan diharapkan untuk melatih HOTS peserta didik sehingga memenuhi tuntutan kompetensi abad 21 dan hasil belajar menjadi lebih baik.